The great panda tale - Buller, Laura (Dorling Kindersley readers. Beginning to read alone., 2014)
Introduces facts about pandas, including what they eat and how they grow, and follows Louise and the rest of the zoo crew as they eagerly await the arrival of a new baby panda.